A population-based study of the incidence of laboratory-confirmed Clostridium difficile infections and their recurrence in the Italian province of Udine. (February 2020) - Valent, Francesca
Abstract: Clostridium difficile infections (CDI) are a frequent cause of healthcare-associated infection and are also increasingly described in the outpatient setting. Epidemiological data in Italy have been collected through hospital-based study designs. We aimed at studying the epidemiology of laboratory-confirmed CDI through a population-based analysis in the Italian 500, 000-inhabitant province of Udine. Various health administrative databases were linked at the individual patient level through an anonymous stochastic key: laboratory tests, hospital discharges, nursing homes, drug prescriptions. The incidence of CDI in 2018 was calculated as new cases per 100, 000 inhabitants and, for cases diagnosed during a hospital or nursing home stay, per 1000 patient admissions and per 10, 000 patient-days. The frequency of recurrent infections was also estimated. In the population of Udine, 240 positive tests were observed, corresponding to 225 infection episodes and 185 persons (35 new cases/100, 000 population-year). 75.1% of CDI episodes were diagnosed during hospital stays, 8.9% during nursing home stays, and 16.0% in non-institutionalized persons. Among hospital inpatients, the incidence was 2.03/1000 admissions and 2.85/10, 000 patient-days; in nursing homes, there were 3.22 cases/1000 admissions and 1.42/10, 000 patient-days. 15% of patients had at least one recurrence. Our results are consistent with international incidence estimates and show higher incidence and frequency of recurrence than those reported in a previous hospital-based study conducted in the Hospital of Udine providing insights for diagnosis and prevention of CDIs. Highlights: This is a population-based study of C. difficile infections in an Italian area. Linkage of anonymous administrative databases was performed. Infections analyzed were laboratory-confirmed. In-hospital incidence was higher than previously reported in this area. In-hospital incidence was consistent with international literature.